Estimating Mandibular Motion Based on Chin Surface Targets During Speech. - Green, Jordan R.; Wilson, Erin M.; Wang, Yu-Tsai; Moore, Christopher A. (Journal of Speech, Language & Hearing Research, 2007)
Purpose: The movement of the jaw during speech and chewing has frequently been studied by tracking surface landmarks on the chin. However, the extent to which chin motions accurately represent those of the underlying mandible remains in question. In this investigation, the movements of a pellet attached to the incisor of the mandible were compared with those of pellets attached to different regions con the chin. Method: Ten healthy talkers served as participants. Three speaking contexts were recorded from each participant: word, sentence, and paragraph. Chin position errors were estimated by computing the standard distance between the mandibular incisor pellet and the chin pellets. Results: Relative to the underlying mandible, chin pellets moved with an average absolute and relative error of 0.81 mm and 7.30%, respectively. The movements of chin and mandibular pellets were tightly coupled in time. Conclusion: The chin tracking errors observed in this investigation are considered acceptable for descriptive studies of oromotor behavior, particularly in situations where mandibular placements are not practical (e.g., young children or edentulous adults). The observed amount of error, however, may not be tolerable for fine-grained analyses of mandibular biomechanics. Several guidelines are provided for minimizing error associated with tracking surface landmarks on the chin. Reprinted by permission of the publisher.